The effect of emotion on word processing in Persian speaking children - Salehi, Sousan; Khatoonabadi, Ahmad Reza; Ashrafi, Mahmoud Reza; Mohammadkhani, Ghasem; Maroufizadeh, Saman; Majdinasab, Fatemeh (Iranian Journal of Child Neurology, 2018)
Objectives: Emotion is a key component in language processing, but it is controversy how emotional content words process in children. The aim of the present study is investigating the effect of arousal and valence on word familiarity, comprehension, use and emotional content recognition. As secondary goal, a list of emotional content words for this age was prepared in Persian. Materials and methods: Emotional words, from adult emotional words list, were categorized in 5groups according their scores in arousal and valence. Evaluation of familiarity, use, comprehension and emotional content recognition of these words was conducted with a prepared checklist in 60 seven-year-old children by speech and language pathologist. Results: Neutral words gained the highest score in familiarity, use, comprehension and emotional content recognition (the mean=0.74). Afterward, there were the emotional words with high valence, calm (the mean=0.64) and happy (the mean=0.52). Finally it was found the low score for valence emotional words, sad (the mean=0.46) anxious (the mean =0.43) in end of score rating. Interestingly, there was a significant difference between all word groups in four aspects (p-value<0.001). Though, differences between boys and girls in four aspects were not significant (p-value>0.001). Conclusion: It was shown that neutral words are better comprehended and expressed than emotional words. More importantly, valence is more effective than arousal in emotional words. It is noteworthy gender was not a determinant factor in all of the aspects. An emotional word list which is comprehensible for children in Persian language was prepared.